The palace of Eros - De Robertis, Carolina (Primero Sueño Press, Atria, 2024)
"A bold retelling of the traditional Greek myth of Psyche and Eros through a queer and feminist lens, grappling with the complex and thorny questions of how to harness the power of female and queer joy and cultivate freedom in a world that seeks to cage us"--